The Role of Working Memory and Attention in Older Workers’ Learning - Angelopoulou, Effrosyni; Karabatzaki, Zoi; Drigas, Athanasios (International Journal of Advanced Corporate Learning (iJAC), 2021)
Nowadays, the aging workforce constitutes a worldwide reality in developed countries due to the population aging phenomenon. Consequently, it becomes urgent for the older workers’ learning to be enhanced for their personal development first, and then for the general progress of the organization. Working memory and attention play a crucial supporting role in older workers’ learning and contribute significantly to their active work life. This article presents the concepts of working memory and attention and their intertwined relationship highlighting their important role in the aging workforce learning. Alongside, the presented theoretical aspects may give the trigger for the greater interest for further research and study of key factors in working environments, which may affect the working memory and attention functioning in older workers, so that to be integrated into the future planning of corporate learning programs.